Soil Erosion Prediction Using GIS and RUSLE: Study at Sampean Watershed - Faisol, Arif; Indarto, Indarto (JOURNAL OF TROPICAL SOILS, 2010)
Soil Erosion Prediction Using GIS and RUSLE: Study at Sampean Watershed (A Faisol and Indarto): Erosion is oneÂ  factor that cause soil degradation in Indonesia. RUSLE (Revised Universal Soil Loss Equation) is widely used to predict average annual rate of soil erosion. This research integrate the Revised Universal Soil Loss Equation (RUSLE) and Geographic Information System (GIS) to predict potential soil erosion losses. Study was conducted at Sampean Watershed where located in Eastern part of East Java. Firstly, GIS layer was obtained from available database that cover East Java Province. All treatment of GIS layer was done using Mapwindows GIS. Furthermore, RUSLE method was used to predict rate of soil erosion from GIS layer treated previously.Â  Results showed that up to 82% (102,921 ha) area of the watershed have tolerable soil erosion rate.